Milk yield and composition a function of feeding of crossbred Holstein x Zebu cows confined under experimental conditions in Brazil - Meta-analysis Produção e composição do leite em função da alimentação de vacas mestiças Holandês x Zebu confinadas em condições experimentais no Brasil - Metanálise - Alessio D.R.M.* (2019)
© 2019 Universidade Federal de Minas Gerais.The aim was to evaluate diet composition factors that may interfere with intake, digestibility, milk yield and composition of crossbred Holstein x Zebus cows confined under Brazilian experimental conditions. The meta-analysis was used for the survey of scientific works of public domain, covering the period from January 2000 to December 2015. The database consisted of 40 experiments with 159 treatments, involving 735 lactating cows. The voluntary intake of total digestible nutrients (TDN) is compromised by the acid detergent fiber (FAD) content of the diet, related to dry matter digestibility (DM) and neutral detergent fiber (NDF), affecting dietary efficiency (DE). The relation of the non-fibrous carbohydrate (NFC) content of the diet with the lactose content and the effect of the DM diet content and the high NDF content on the voluntary intake are specific characteristics of the types of roughage used. Dietary NDT intake is affected by the digestibility of DM and, mainly, NDF, depending on the proportion and characteristics of the nutrients used in the diet, and these factors have an impact on dietary efficiency, as well as on milk composition.